ADVANCING APPROACHES TO STRENGTHEN STUDENTS’ PROFESSIONAL SKILLS IN THE DIGITAL ERA - Tadjiboyev Kamoldin Abdusadikovich (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract In the rapidly evolving digital landscape, the development of students’ professional skills requires innovative and adaptive teaching approaches. This paper explores advanced methodologies that integrate digital tools and modern educational strategies to enhance students’ readiness for the workforce. Emphasizing blended learning, competency-based education, and technology-driven instruction, the study highlights how digitalization fosters personalized, interactive, and practical learning experiences. Additionally, it addresses challenges such as digital literacy gaps and the need for continuous curriculum adaptation. By leveraging digital advancements, educators can equip students with the essential competencies required in today’s professional environment.